2017
DOI: 10.2337/db17-0578
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-Cell–Derived IP-10/CXCL10 Isletokine Mediates Early Loss of Graft Function in Islet Cell Transplantation

Abstract: Pancreatic islets produce and secrete cytokines and chemokines in response to inflammatory and metabolic stress. The physiological role of these “isletokines” in health and disease is largely unknown. We observed that islets release multiple inflammatory mediators in patients undergoing islet transplants within hours of infusion. The proinflammatory cytokine interferon-γ–induced protein 10 (IP-10/CXCL10) was among the highest released, and high levels correlated with poor islet transplant outcomes. Transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 53 publications
2
42
1
Order By: Relevance
“…CXCL10 has been demonstrated to promote immune infiltration and destruction of islets in autoimmune models (37), and it is highly expressed in insulitic lesions in patients with recent-onset T1D (52). Beyond this, CXCL10 promotes immune infiltration in islet isografts (53) and allografts (38,54), and is linked to poor clinical islet transplant outcomes (9,55). Suppression of CXCL10 is significant as neutralization of CXCL10 can prolong graft survival in our model.…”
Section: Figure 5 Administration Of Anti-cd25 Ablates and Rapamycinmentioning
confidence: 81%
“…CXCL10 has been demonstrated to promote immune infiltration and destruction of islets in autoimmune models (37), and it is highly expressed in insulitic lesions in patients with recent-onset T1D (52). Beyond this, CXCL10 promotes immune infiltration in islet isografts (53) and allografts (38,54), and is linked to poor clinical islet transplant outcomes (9,55). Suppression of CXCL10 is significant as neutralization of CXCL10 can prolong graft survival in our model.…”
Section: Figure 5 Administration Of Anti-cd25 Ablates and Rapamycinmentioning
confidence: 81%
“…Originally, it was assumed that infiltrating immune cells were sole producers of proinflammatory cytokines in islets. However, flow cytometry, immunohistochemistry, and laser capture analysis studies revealed that the islet endocrine cells also produce proinflammatory mediators that can elicit immune cell responses [47][48][49][50][51][52][53][54][55]. In fact, the islet cells produce and release dozens of isletokines that can be detected in the blood circulation upon infusion that correlate with transplant outcomes [55,56].…”
Section: Islet Contributions To Acute Graft Inflammationmentioning
confidence: 99%
“…However, flow cytometry, immunohistochemistry, and laser capture analysis studies revealed that the islet endocrine cells also produce proinflammatory mediators that can elicit immune cell responses [47][48][49][50][51][52][53][54][55]. In fact, the islet cells produce and release dozens of isletokines that can be detected in the blood circulation upon infusion that correlate with transplant outcomes [55,56]. In particular, HMGB1, MCP-1 and IP-10 are highly expressed and released in damaged or stressed islets and play a key role in initiating acute inflammation in transplanted islets [55,[57][58][59][60][61][62].…”
Section: Islet Contributions To Acute Graft Inflammationmentioning
confidence: 99%
See 2 more Smart Citations